Enzymatic dyeing of wool - Tzanov, Tzanko (2002)
This study reports for the dyeing of wool using an enzymatic system comprising laccase (EC 1.10.3.2), dye precursor - 2,5-diaminobenzenesulfonic acid and dye modifiers – cathehol and resorcinol. The effect of the process variables - reaction time, enzyme and modifiers concentration on fabrics colour was studied, according to an appropriate experimental design. Different hues and depth of shades could be achieved varying the concentration of the modifiers and the time of laccase treatment. The duration of the enzymatic reaction appeared to be the most important factor in the dyeing process. Thus the dyeing process, performed at low temperature and mild pH, was advantageous in terms of reduced enzyme and chemicals dosage. The ability of the laccases to generate colour “in situ” from originally non-coloured, low-molecular substances, appears as an alternative to the conventional dyeing processes. The dye precursors can be used alone or in combination with suitable modifier (coupler) – another phenolic compound, which together with the dye precursor will enlarge the colour pallet achieved in the enzymatic dyeing.